Effect of subject task on contralateral suppression of click evoked otoacoustic emissions - de Boer, Jessica; Thornton, A. Roger D. (Hearing research, 2007)
Contralateral suppression of click evoked otoacoustic emissions (CEOAEs) is widely used as a non-invasive measure of the activity of the (uncrossed) medial olivocochlear bundle (MOCB). There is evidence that the uMOCB receives descending input from the cortex, potentially mediating top–down control during higher order processing. This study investigated whether the contralateral suppression measure is affected by top–down influences during different tasks performed by the participants during recording. Suppression of CEOAEs evoked at 50 and 60 dB SPL was measured under four different task conditions: (1) no task; (2) passive visual (watching a silent subtitled DVD); (3) active visual (responding to visually presented sums); (4) active auditory (detecting tone pips embedded in the evoking click train). The most significant effect of task was found on the recording noise, with both the passive visual and the active auditory task producing significantly lower noise levels than the no task condition. In the passive visual task, this was associated with a reduced inter-subject variability, which enhanced the effect size relative to the no task condition. A main effect of subject task was also found on the change in CEOAE I/O slope due to contralateral noise. This effect reflected a significantly smaller suppression during the active auditory task compared to the no task condition, leading to a reduced effect size. No significant difference in suppression strength between the no task condition and the two non-auditory tasks was observed, suggesting that the main effect of task reflects a specific effect of auditory attention. The data suggest that MOCB activity is inhibited due to top–down influences when selective attention is focussed on the ipsilateral ear.